Experimental Investigations of Viscous Heating Effect of Thermocouples under Focused Ultrasound Applications - (:unkn) unknown (IEEE, 2017)
Realization of temperature characterization on focused ultrasound treatment devices by using tissue-mimicking phantom systems (Tissue-Mimicking Material, TMM) is indispensible in pre-clinical studies. In this survey, in order to examine the viscous heating effect of thermocouples, temperature rise due to excitation of a HIFU transducer has been measured by using two different types of T-type thermocouples embedded inside the TMM. In order to obtain the temperature values from the thermocouples more effectively, a PC-based multi-channel data acquisition and monitoring interface were developed by using LabVIEW graphical development platform. Measurements were carried out inside a TMM which has characteristics like human liver tissue. Temperature rise has been characterized for the different input ultrasonic powers (25 W, 38 W and 50 W) and frequencies (1,1 MHz and 3.3 MHz) and the time intervals applied (1 s, 2 s and 3 s). The temperature values obtained from two different types of T-type thermocouple were compared to each other and discrepancies between these two different thermocouple measurements were shown with the study.
Keywords: Viscous heating effect; Therapeutic ultrasound; HIFU; Thermocouple; Lab VIEW; TMM; HIFU